Characterizing microbial communities and processes in a modern stromatolite (Shark Bay) using lipid biomarkers and two-dimensional distributions of porewater solutes - Pages, Anais; Grice, Kliti; Vacher, M.; Welsh, D.; Teasdale, P.; Bennett, W.; Greenwood, Paul (Wiley-Blackwell Publishing Ltd., 2014)
Modern microbial mats are highly complex and dynamic ecosystems. Diffusive equilibration in thin films (DET) and diffusive gradients in thin films (DGT) samplers were deployed in a modern smooth microbial mat from Shark Bay in order to observe, for the first time, two-dimensional distributions of porewater solutes during day and night time. Two-dimensional sulfide and alkalinity distributions revealed a strong spatial heterogeneity and a minor contribution of sulfide to alkalinity. Phosphate distributions were also very heterogeneous, while iron(II) distributions were quite similar during day and night with a few hotspots of mobilization. Lipid biomarkers from the three successive layers of the mat were also analysed in order to characterize the microbial communities regulating analyte distributions. The major hydrocarbon products detected in all layers included n-alkanes and isoprenoids, whilst other important biomarkers included hopanoids. Phospholipid fatty acid profiles revealed a decrease in cyanobacterial markers with depth, whereas sulfate-reducing bacteria markers increased in abundance in accordance with rising sulfide concentrations with depth. Despite the general depth trends in community structure and physiochemical conditions within the mat, two-dimensional solute distributions showed considerable small-scale lateral variability, indicating that the distributions and activities of the microbial communities regulating these solute distributions were equally heterogeneous and complex.